Intangible heritages: historical perspectives of Yahoode (Hadiya New Year) festival of Hadiya people, South Central Ethiopia - Tesfaye Tadesse; Mesert Bekele; Mamo Tumito; Habte Fikre (Cogent Social Sciences, 2024)
Historical account of the festival is utterly embedded in the culture and history of the existing society. The Yahoode festival of the Hadiya people of south-central Ethiopia is a historically and culturally significant New Year festival deemed an intangible cultural heritage. Much of the festival is documented through oral traditions and, at best, written in the Amharic or other Ethiopian languages. Through interviews and snowball sampling, the article maps historical perspectives of the festival and finds it endowed with socio-economic and cultural values that balance individual and community values. These include respect for one another, industriousness, the culture of saving, building peace, active participation and wise use of time. However, the article revealed that there has been change and continuity in the celebration in the course of history, it foregrounds the significance of the Yahoode festival in the cultural and economic life of the Hadiya people and identifies its socio-economic opportunities.